Biofortification of oil quality, yield, and nutrient uptake in Indian mustard (Brassica juncea L.) by foliar application of boron and nitrogen - Dhaliwal, Salwinder Singh; Sharma, Vivek; Shukla, Arvind Kumar; Kaur, Manmeet; Verma, Vibha; Sandhu, Prabhjodh Singh; Alsuhaibani, Amnah Mohammed; Gaber, Ahmed; Hossain, Akbar (Frontiers in Plant Science, 2022)
Indian mustard (Brassica juncea L.) is an essential oilseed crop which offers important nutrients to human beings. But, the concurrent micronutrient deficiencies including boron (B), sulphur (S) and nitrogen (N) could pose a significant threat to public health. Therefore, this study evaluated the influence of B and N foliar application on quality parameters, yield, nutrient concentration and their uptake as well as economics of Indian mustard cultivation so as to enhance its nutritional quality. In the experiment, different concentrations of borax and urea at flowering and capsule formation stage were applied to Indian mustard. The foliar application of RDF + Borax (1.0%) + Urea (1.0%) at flowering and capsule formation stage (treatment T9) was highly efficient in increasing food quality parameters such as crude fibre, total soluble solids (TSS) and protein content with maximum values of 3.77%, 24.9% and 27.53%, respectively. Also, maximum yields of grain as well as stover for treatment T9 were 1376 kg ha-1 and 6625 kg ha-1, respectively. Similarly, the results for B. S and N concentration in grain (27.71 mg kg-1, 17.69 mg kg-1 and 2.35%) as well as stover (25.92 mg kg-1, 17.31 mg kg-1 and 0.33%) were maximum in treatment T9. Also, B, S and N uptake by grain (38.18 g ha-1, 24.40 g ha-1 and 32.05 Kg ha-1) and stover (172.55 g ha-1, 115.44 g ha-1 and 21.99 Kg ha-1) were maximum for the treatment T9 involving borax (1.0%) + urea (1.0%) at flowering and capsule formation stage. Whereas, the concentration and uptake decreased in the treatments involving the sole application of borax and urea. Therefore, the application of borax (1.0%) and urea (1.0%) at flowering and capsule formation stage significantly improved the quality parameters, grain and stover yield, nutrient concentration and uptake over control and could be used in order to alleviate the B. S and N deficiency in Indian mustard.